CGIAR report to the twelfth session of the intergovernmental technical working group on plant genetic resources for food and agriculture - CGIAR Genebank Initiative (2024)
This report was prepared by CGIAR in response to an invitation from the Secretariat of the FAO Commission on Genetic Resources for Food and Agriculture. It is structured to correspond, in general, to agenda items 3-5 of the Twelfth Session of the Intergovernmental Technical Working Group on Plant Genetic Resources (ITWG-PGRFA).